2011
DOI: 10.1021/jp208573y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of the C2 Proton in Promoting Low Viscosities and High Conductivities in Imidazolium-Based Ionic Liquids: Part I. Weakly Coordinating Anions

Abstract: 1,3-Disubstituted imidazolium ionic liquids have been the subject of numerous theoretical and experimental studies due to their low viscosity-often the very lowest for any given cation/anion family. One of the mysteries in the imidazolium family of salts is the sharp increase in viscosity that is observed on methylating at the C2 position in the ring. In the nonmethylated case, the C2 proton is observed to be distinctly acidic and, where this is undesirable, substitution of the C2 position removes the problem,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 47 publications
8
114
1
Order By: Relevance
“…In the real liquid, a distribution of several cation/anion configurations will be present simultaneously [43], and the sketch must be seen as one example of what the data suggest exists in larger amounts. in computational studies [4,5,7,28,29,38]. This suggests that the above findings represent a rather universal phenomenon.…”
Section: Nmr Spectramentioning
confidence: 65%
See 2 more Smart Citations
“…In the real liquid, a distribution of several cation/anion configurations will be present simultaneously [43], and the sketch must be seen as one example of what the data suggest exists in larger amounts. in computational studies [4,5,7,28,29,38]. This suggests that the above findings represent a rather universal phenomenon.…”
Section: Nmr Spectramentioning
confidence: 65%
“…This is particularly true for the molecular anions, [BF 4 − ] and [PF 6 − ]. Consequently, the overall molecular system gains symmetry when the C (2) number of other dialkylimidazolium ILs, e.g., NTf 2 and other halogenide anions, and in computational studies [4,5,7,28,29,38]. This suggests that the above findings represent a rather universal phenomenon.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[34][35][36] Recent studies have shown that dispersion forces play an unexpectedly important role. [35][36][37] Additionally, functional parts of the molecule, such as hydrogen bonds 23,36,[38][39][40][41][42][43] or alkyl chain length, 6,23,29 may contribute to a low melting point or low viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Upon comparison electrolyte B with electrolyte A, which contains PMII, which is less viscous and transports ions faster than DMPII, [21] GuNCS (0.1 m), and LiI (0.5 m), we note that the efficiency of TFRS-2 a (h = 9.11 %) is higher than that reported for TFRS-52 a under identical conditions (h = 8.92 %). This trend is reversed if electrolyte A is used.…”
Section: Device Performance Characteristicsmentioning
confidence: 71%